2022
DOI: 10.1111/jvim.16512
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the blood neutrophil‐to‐lymphocyte ratio as a biomarker for meningoencephalitis of unknown etiology in dogs

Abstract: Background: The neutrophil-to-lymphocyte ratio (NLR) has been identified as a biomarker in several inflammatory and autoimmune diseases. Multiple sclerosis (MS) has been found to be associated with changes in the NLR in humans.Objectives: To examine the diagnostic value of the NLR in meningoencephalitis of unknown etiology (MUE) in dogs.Animals: Thirty-eight MUE dogs, 20 hydrocephalic dogs, 10 brain tumor (BT) dogs, 32 idiopathic epilepsy (IE) dogs, and 41 healthy dogs.Methods: Retrospective study. Medical rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 36 publications
0
11
1
Order By: Relevance
“…7,11 Recently, NLR has been studied in dogs with pancreatitis, meningoencephalitis of unknown cause, and inflammatory bowel disease, and a significant difference was confirmed when compared with the healthy group. [22][23][24] In humans, neutrophilia has been identified in patients with heart disease and clinical symptoms. 4 Lymphopenia is associated with a poor prognosis in heart failure patients.…”
Section: Discussionmentioning
confidence: 99%
“…7,11 Recently, NLR has been studied in dogs with pancreatitis, meningoencephalitis of unknown cause, and inflammatory bowel disease, and a significant difference was confirmed when compared with the healthy group. [22][23][24] In humans, neutrophilia has been identified in patients with heart disease and clinical symptoms. 4 Lymphopenia is associated with a poor prognosis in heart failure patients.…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted by Conway et al (2021) demonstrates that dogs with pneumonia had median 16.7 NEU/LYM and the NEU/LYM did not differ significantly between the survivors and non-survivors, nor did total WBC count or NEU count. Park et al (2022) also showed the NEU/LYM could be a biomarker for diagnosing meningoencephalitis of unknown etiology and distinguishing it from other intracranial diseases in dogs. The median NEU/LYM ratio was 6.08 in the meningoencephalitis of unknown etiology (Park et al, 2022).…”
Section: Discussionmentioning
confidence: 95%
“…Park et al (2022) also showed the NEU/LYM could be a biomarker for diagnosing meningoencephalitis of unknown etiology and distinguishing it from other intracranial diseases in dogs. The median NEU/LYM ratio was 6.08 in the meningoencephalitis of unknown etiology (Park et al, 2022). In the present study, we found a median NEU/LYM value as 31.9 in dogs with CDV infection which found significantly higher (P .000) when comparing the control median value of 6.39.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Sometimes it may also be difficult to determine whether the elevation of specific biomarkers coincide or precede clinical deterioration, thereby limiting their diagnostic utility. A further limitation is that, with some exceptions ( 105 ), comparisons have often not been made between findings in MUO and other neurological conditions. On the other hand, the more sophisticated technique of “immunosignaturing,” which determines patterns of serum antibody binding to a large array of peptides, was shown to discriminate between healthy dogs, dogs with brain tumors and dogs with MUO, including in a validation set ( 109 ), suggesting promise in discriminating different types of MUO in future (see below).…”
Section: Discussionmentioning
confidence: 99%